Application of Energy-Saving Distiller for Standardized Patchouli Oil Production in Patchouli Oil SME in Kulon Progo - Karna Wijaya; Widi Kurniawati; Nasih Widya Yuwono; Farida Farida (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2020)
Patchouli oil is one of the export commodities with high economic value that attracts attention in the raw material business. To be marketed domestically as well as internationally, patchouli oil must meet the Indonesian National Standard (SNI). Various patchouli oil processing techniques have been developed by researchers but only a few that meet the requirements of SNI. In this study, patchouli leaves were processed using an energy-saving distiller equipped with heat insulators. Patchouli oil was then treated using bentonite-NaHCO3 composite adsorbent which was synthesized through a hydrothermal process followed by calcination. The program was executed by preparing of the distiller and adsorbent before applying them to Surya Wulan patchouli oil processing SME. The adsorbent was prepared and analyzed at the Physical Chemistry Laboratory and the distiller was tested in CV. Fruitanol Energy, Yogyakarta. The result showed that the distiller has a capacity of 15 kg, which can save costs up to 35.5% and 33.3% more efficient in time compared to the conventional technology in Surya Wulan SME. Patchouli oil produced successfully met SNI quality requirements and was certified by LPPT UGM. Furthermore, the adsorbent produced was able to reduce around 80% of the acid number of crude patchouli oil.